Good Corporate Governance dan Tax Avoidance : Systematic Literature Review - Maharani, Eriza Nabila; Akbar, Fajar Syaiful (MDP Student Conference, 2025)
Tax avoidance is a series of legitimate actions aimed at reducing tax liabilities. Although legally tax avoidance does not violate the rules, this practice is often considered unethical because it can reduce the potential for state tax revenues that should be used for the public interestThis research seeks to examine the potential of effective corporate governance in preventing tax avoidance through a systematic review of existing empirical studies.This summary helps the author understand that various aspects of good corporate governance such as the audit committee, board of directors, board of commissioners, and ownership structure have a significant impact on tax avoidance in the business